ANALISIS KEMANDIRIAN DAN EFEKTIVITAS KEUANGAN DAERAH KABUPATEN BENGKALIS - Firdaus Firdaus (Bertuah: Journal of Sharia and Islamic Economics, 2020)
The purpose of this study was to examine the financial performance of the district Bengkalis by  the area financial independence ratio in the 2014-2018 budget period and the area financial effectiveness ratio in the 2014-2018 budget period. This research is a descriptive study and the data is secondary data obtained from Bengkalis. The data analysis technique used is the ratio analysis technique to measure the financial performance of goverment. The study show that 1) The area financial independency ratio on average  at 6.36%-9.64% with a very low category 2).The effectiveness ratio on average at 59.31%-90.02%, overall with a tendency not effective. Implications for institution life are policy makers need to continue and increase the Locally Generated Revenue with maximizing the potential of the area. Keywords: Financial Performance, Independence Tatio, The Ratio of Effectiveness